2017
DOI: 10.1242/dev.144907
|View full text |Cite|
|
Sign up to set email alerts
|

Distinct roles of neuroepithelial-like and radial glia-like progenitor cells in cerebellar regeneration

Abstract: Zebrafish can regenerate after brain injury, and the regenerative process is driven by resident stem cells. Stem cells are heterogeneous in the vertebrate brain, but the significance of having heterogeneous stem cells in regeneration is not understood. Limited availability of specific stem cells might impair the regeneration of particular cell lineages. We studied regeneration of the adult zebrafish cerebellum, which contains two major stem and progenitor cell types: ventricular zone and neuroepithelial cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 43 publications
(94 reference statements)
2
68
0
1
Order By: Relevance
“…However, RG in the telencephalon, hypothalamus and spinal cord of adult zebrafish function as neural stem cells in both adult and regenerative neurogenesis (Adolf et al, ; Gorsuch et al, ; Hui, Nag, and Ghosh, ; Johnson et al, ; Kishimoto et al, ; Kizil et al, 2012; Kroehne, Freudenreich, Hans, Kaslin, and Brand, ; Mokalled et al, ; Raymond et al, ). Moreover, in the cerebellum, NE, but not RG, operate as neural stem cells in both physiological and regenerative conditions (Bae et al, ; Kaslin, Kroehne, Ganz, Hans, & Brand, ). RG and NE have different capacities as neural stem cell in different regions of the CNS and it is not well known how the regenerative abilities of RG and NE as neural stem cells are regulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, RG in the telencephalon, hypothalamus and spinal cord of adult zebrafish function as neural stem cells in both adult and regenerative neurogenesis (Adolf et al, ; Gorsuch et al, ; Hui, Nag, and Ghosh, ; Johnson et al, ; Kishimoto et al, ; Kizil et al, 2012; Kroehne, Freudenreich, Hans, Kaslin, and Brand, ; Mokalled et al, ; Raymond et al, ). Moreover, in the cerebellum, NE, but not RG, operate as neural stem cells in both physiological and regenerative conditions (Bae et al, ; Kaslin, Kroehne, Ganz, Hans, & Brand, ). RG and NE have different capacities as neural stem cell in different regions of the CNS and it is not well known how the regenerative abilities of RG and NE as neural stem cells are regulated.…”
Section: Discussionmentioning
confidence: 99%
“…In the adult telencephalon, radial glia (RG) operate as neural stem cells in both physiological and regenerative conditions and Notch and FGF signaling have been reported to control the ability of RG to generate new neurons in both conditions (Ganz, Kaslin, Hochmann, Freudenreich, & Brand, ; Kishimoto, Shimizu, & Sawamoto, ). However, few studies have examined other parts of the brain, such as the olfactory bulb, optic tectum, and cerebellum (Galant et al, ; Kaslin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…During neuronal regeneration in telencephalon, it was shown that radial glia (RG) function as neural stem cells (Baumgart, Barbosa, Bally‐Cuif, Götz, & Ninkovic, ; Diotel et al, ; Kroehne et al, ; Kyritsis et al, ). Recently, neuronal regeneration has also been reported to occur in the cerebellum (Kaslin, Kroehne, Ganz, Hans, & Brand, ; Zupanc, Hinsch, & Gage, ). However, in cerebellar regeneration, primarily neuroepithelial‐like stem cells (NE), rather than the RG, serve as neural stem cells after stab injury (Kaslin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, neuronal regeneration has also been reported to occur in the cerebellum (Kaslin, Kroehne, Ganz, Hans, & Brand, ; Zupanc, Hinsch, & Gage, ). However, in cerebellar regeneration, primarily neuroepithelial‐like stem cells (NE), rather than the RG, serve as neural stem cells after stab injury (Kaslin et al, ). Thus, RG may have region‐specific roles throughout the CNS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation